Chitosan hydrogel anchored phthalocyanine supported metal nanoparticles: Bifunctional catalysts for pollutants reduction and hydrogen production. (15th June 2023) - Akhtar, Kalsoom; Khan, Mohammad Sherjeel Javed; Bakhsh, Esraa M.; Kamal, Tahseen; Asiri, Abdullah M.; Khan, Sher Bahadar
Abstract: Metal nanoparticles possess high catalytic activity in various organic transformation reactions. A catalyst must be recovered and re-used effectively and economically to lower the overall reaction cost. The recovery of a catalyst remains a challenge due to their extreme small size. In this research work, catalytic metal nanoparticles were synthesized on Zn-phthalocyanine (ZnPc) and chitosan hydrogel (CH) composite which acts as catalyst support. The ZnPc-CH support facilitate the easy recovery of the loaded metal nanoparticles. Metal nanoparticles (M 0 ) based on Cu 0, Ag 0, Ni 0, Co 0 and Fe 0 were decorated inside and on ZnPc-CH hydrogel surface. The developed M 0 @ZnPc-CH were utilized for the enhanced selective reduction of toxins and hydrogen production by methanolysis and hydrolysis of NaBH4 . Effective catalytic reduction and hydrogen generation was successfully achieved with Co 0 @ZnPc-CH and ZnPc-CH. Under optimized conditions, Co 0 @ZnPc-CH showed complete reduction of 4-nitrophenol (4-NP) in 8.0 min with the fast 4-NP reduction kinetics ( K  = 0.611 min −1 ). Among the developed catalysts, ZnPc-CH showed fast H2 generation with high H2 generation rate (HGR = 4100 mLg −1 min −1 ) under optimized conditions. Metal leaching from Co 0 @ZnPc-CH was negligible during recycling of the catalyst, suggesting that it could be implemented to 4-NP treatment from real water samples. Similarly, ZnPc-CH could produce same quantity of H2 throughout 4 continuous cycles of durability testing without any deactivation and leaching and ZnPc-CH showed high stability, indicating the effectiveness of the catalyst to be applied for H2 production on large scale. Graphical abstract: Image 1 Highlights: ZnPc-CH hydrogel anchored and remarkably disperse MNPs. Co 0 @ZnPc-CH is efficient catalyst for pollutants reduction. ZnPc-CH hydrogel is efficient catalyst for hydrogen production. Efficient catalyst in real samples.